Fermentasi pelepah sawit dengan bakteri asam laktat: Lactobacillus plantarum dan Pediococcus pentosaceus - Syarifah Nur Halimah; Mansyur; Ruslan Abdul Gopar (Fakultas Pertanian Universitas Majalengka, 2024)
Palm fronds are a crop commodity that generates substantial amounts of waste that is utilized in agricultural industries. Palm frond waste can be processed into animal feed and serve as an effort to reduce environmental pollution caused by palm oil production. Given its potential, it warrants further testing, but it contains numerous detrimental anti-nutritional compounds if consumed directly by livestock. Therefore, using proximate analysis, fermentation processing using bacteria such as Lactobacillus plantarum and Pediococcus pentosaceus must be done. This study was conducted at the Laboratory for Development of Industrial Agricultural & Biomedical Techniques (LAPTIAB), National Research and Innovation Agency (BRIN) from November 1, 2023 to February 29, 2024. The experimental design was a complete randomized block design including treatments like control, Lactobacillus plantarum, Pediococcus pentosaceus, and consortium analyzed via DMRT (Duncan’s Multiple Range Test). Results showed that adding Lactobacillus plantarum to palm fronds resulted in the lowest reduction of crude fibre content by 45.59%, without affecting crude protein, crude fat, or nitrogen-free extract contents. It can be concluded that using Lactobacillus plantarum and Pediococcus pentosaceus in the fermentation process of palm fronds has no natural effect on the content of crude protein, crude fat, and BETN. However, the lactic acid bacteria can reduce the content of crude fibre fermented palm fronds.